De novo NAD+ synthesis enhances mitochondrial function and improves health. (15th November 2018) - Katsyuba, Elena; Mottis, Adrienne; Zietak, Marika; Franco, Francesca; Velpen, Vera; Gariani, Karim; Ryu, Dongryeol; Cialabrini, Lucia; Matilainen, Olli; Liscio, Paride; Giacchè, Nicola; Stokar-Regenscheit, Nadine; et al.
Abstract Nicotinamide adenine dinucleotide (NAD+ ) is a co-substrate for several enzymes, including the sirtuin family of NAD+ -dependent protein deacylases. Beneficial effects of increased NAD+ levels and sirtuin activation on mitochondrial homeostasis, organismal metabolism and lifespan have been established across species. Here we show that α-amino-β-carboxymuconate-ε-semialdehyde decarboxylase (ACMSD), the enzyme that limits spontaneous cyclization of α-amino-β-carboxymuconate-ε-semialdehyde in the de novo NAD+ synthesis pathway, controls cellular NAD+ levels via an evolutionarily conserved mechanism inCaenorhabditis elegans and mouse. Genetic and pharmacological inhibition of ACMSD boosts de novo NAD+ synthesis and sirtuin 1 activity, ultimately enhancing mitochondrial function. We also characterize two potent and selective inhibitors of ACMSD. Because expression of ACMSD is largely restricted to kidney and liver, these inhibitors may have therapeutic potential for protection of these tissues from injury. In summary, we identify ACMSD as a key modulator of cellular NAD+ levels, sirtuin activity and mitochondrial homeostasis in kidney and liver. Genetic or pharmacological inhibition of α-amino-β-carboxymuconate-ε-semialdehyde decarboxylase increases NAD+ and improves mitochondrial function in nematodes and mice, and may have therapeutic potential in kidney and liver disease.